Fibroblast Growth Factor 18 Increases the Trophic Effects of Bone Marrow Mesenchymal Stem Cells on Chondrocytes Isolated from Late Stage Osteoarthritic Patients - Zhenyu Zhang; Yan Wang; Mingchao Li; Jiaping Li; Jian Wu (Stem Cells International)
Coculture of mesenchymal stem cells with chondrocytes increases production of cartilaginous matrix. Chondrocytes isolated from late stage osteoarthritic patients usually lost their phenotype of producing cartilaginous matrix. Fibroblast growth factor 18 is believed to redifferentiate OA chondrocyte into functionally active chondrocytes. The aim of this study is to investigate the supportive effects of MSCs on OA chondrocytes and test if FGF18 could enhance the responsiveness of OA chondrocytes to the support of MSCs in a coculture system. Both pellet and transwell co-cultures were used. GAG quantification, hydroxyproline assay, and qPCR were performed. An ectopic models of cartilage formation was also applied. Our data indicated that, in pellets coculture of MSCs and OA chondrocytes, matrix production was increased in the presence of FGF18, comparing to the monoculture of chondrocytes. Results from transwell coculture study showed that expression of matrix producing genes in OA chondrocytes increased when cocultured with MSCs with FGF18 in culture medium, while hypertrophic genes were not changed by coculture. Finally, coimplantation of MSCs with OA chondrocytes produces more matrix than chondrocytes only. In conclusion, FGF18 can restore the responsiveness of OA chondrocytes to the trophic effects of MSCs. Coimplantation of MSCs and OA chondrocytes treated with FGF18 may be a good alternative cell source for regenerating cartilage tissue that is degraded during OA pathological changes.